“C-shaped” anterolateral thigh flap for stomal repair due to recurrence in patients with total laryngectomy - Sakarya, Ahmet Hamdi; Saraç, Ömer; Akdeniz Doğan, Zeynep; Saçak, Bülent (Acta Medica, 2024)
Background: Stomal recurrence after total laryngectomy is one of the most challenging problems in head and neck surgery due to the complexity of its management. The tracheal opening remains deep and caudal after resection, creating a neo stoma that presenting a significant challenge for reconstructive surgery. With this study, we aimed to describe the design of the C-shaped ALT flap to show that it is the ideal design in such a difficult reconstruction. Methods: Five patients who underwent a free ALT flap for defects in the anterior neck wall and airway after resection due to tumor recurrence adjacent to a permanent stoma between 2018-2020 were included in the study. Tumor resection was performed by the Otolaryngology team in all cases. Age, gender, cause of defect, ALT flap size, donor site closure method, number of perforators, ischemia time, flap survival, early complications, and postoperative tracheostomy use and postoperative quality of life assessment were reviewed. Results: 5 male patients were included in the study and the mean age was 63.8. The mean duration between admission and recurrence after laryngectomy was 11.2 months. Flap survival was noted in all patients. The patients did not encounter complications such as tracheostomy-related dehiscence, discharge, fistula, cannulation difficulties due to flap collapse, and mediastinitis during their lifetime. In the follow-ups, one still alive, the mean survival time of the other three patients was four months. We found an average high score in our patients regarding functional scales in QLQ-H&N35 module. Conclusions: The C-shaped ALT flap design provides ease of insertion into a tension-free tracheal-skin suture line and helps to reduce the rates of stoma-related complications and increase the quality of life of the patients.